Psychological Resilience of University Student During Pandemic Covid 19 - Erina Rahmajati; Rinova Cahyandari; Ahmad Zawawi; Vivi Zihrra Octaviani; Maulana Yusuf Ibrahim (Human Sustainability Procedia, 2022)
In dealing with the COVID-19 situation, students can develop instability in mental conditions. But after one year since the first wave of covid-19 pandemic, they also have a new problem-solving pattern. An individual tends to have an adaptation mechanism to stress, especially if the source of the stress is faced for a long time. This mechanism will also form a new psychological resistance called resilience. Therefore, this article will discuss how to describe the condition of psychological resilience in students during the COVID-19 pandemic. This research uses triangulation research method. Where the data collection uses the closing questionnaire method, namely DASS and produces quantitative data in the form of stress levels experienced by students during online lectures. While qualitative data is obtained from the results of data collection using an open questionnaire, where students will answer several open questions according to their conditions. From 181 people who became respondents in this study, after screening based on normal stress levels, 94 respondents were selected. Furthermore, the data of the 94 respondents will be processed for their data regarding their psychological resilience indicators. The result of this research shows that there were other groups who can managed to survive and were under normal stress conditions. This group of students showed that they had succeeded in forming psychological resilience with the ability to recognize emotions and the ability to control their emotions, as well as being able to cope with the stressors they faced. Based on these results, it can be a major concern that groups that are successful in forming resilience can also be a support system for other groups, because one of the problems that causes someone to not succeed in forming psychological resilience is because they do not have a support system that helps them get out of trouble what they went through.